ANALISIS TEORI KEBENARAN ILMU PENGETAHUAN: TANTANGAN KEBENARAN DI ERA POST TRUTH - Muhammad Junaldi Jufri Jufri; Sitoli Mony Mony (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
Truth is a fundamental concept in science that continues to evolve from classical philosophy to the post-truth era. This era is characterized by the dissemination of information that prioritizes emotions and subjective beliefs over objective facts, thus posing a challenge to science because it has the potential to weaken the standards of truth and the scientific method. This article discusses various correspondence, coherence, pragmatic, consensus, semantic, syntactic, and performative theories of truth as tools for filtering and assessing information in the post-truth era. Using a literature study approach, this study examines the development of the concept of truth in the scientific world. The analysis shows that correspondence theory bases truth on conformity with reality, coherence theory emphasizes consistency in knowledge systems, and pragmatic theory measures truth based on its benefits. Consensus theory relies on the agreement of the scientific community, while semantic and syntactic theories analyze the meaning and structure of language in distinguishing facts from disinformation. The performative theory considers a statement to be true if it can create reality. By applying these theories, people can be more critical in assessing the truth, so that science remains the basis for decision-making and information dissemination.